Farin İlavesinin Çini Bünye Özelliklerine Etkisi - Kaftelen, Hülya (Fırat University, 2016)
Bu çalışmada, Bilecik kaoleni, Mihallıçık kili, dolomit ve pudra kuvars karışımından bir çini bünye hazırlanmıştır. Çini bünyelerde hammadde olan dolomit yerine ağırlıkça % 0-15 arasında çimento sektöründe kullanılan farin ilavesi yapılarak 4 farklı çini bünye hazırlanmıştır. Çini bünyeler plastik olarak şekillendirildikten sonra 885 oC, 925 oC ve 975 oC sıcaklıklarda ayrı ayrı pişirilmişlerdir. Çini bünyelerin pişme küçülmesi, su emme ve mukavemet özelliklerine farin ilavesi ve pişirim sıcaklıklarının etkisi incelenmiştir. Pişme mukavemeti, en yüksek değerine (110 kg/cm2) ağırlıkça %15 farin ilaveli 975 oC 'de pişirilmiş numunelerde ulaşılırken, 885 oC'de pişirilmiş farin ilavesiz numunelerde en düşük mukavemet değerine (62 kg/cm2) ulaşılmıştır. Ayrıca, numunelerin su emme değerleri artan pişme sıcaklığı ve farin miktarı ile azalmıştır.

In this study, the chinaware was prepared by the mixture of Bilecik clay, Mihallıçık clay, dolomite and powders quartz. Four different chinawares were prepared by adding farine, which is used in cement industry, between 0- 15 wt.% instead of dolomite used in chinaware as raw material. After the chinawares are shaped plastically and they were separately fired at temperatures of 885 oC, 925 oC ve 975 oC. The effect of farine addition and fired temperatures on the firing shrinkage, water absorption and flexural strength of chinawares were investigated. Flexural strength was reached the maximum value (110 kg/cm2) for sample containing 15 wt.% farine and fired at 975 oC, while the lowest flexural strength (62 kg/cm2) was obtained for the farine free sample fired at 885 oC. Additionally, the water absorption values of samples were decreased with increasing the amount of farine and firing temperature.
Effect of Farine Addition on the Properties of Chinaware Bodies